The Tradition of The Emirate Over The Country: A Comparison Between The Ideas of Imam Al-Mawardi and Law No. 1 Of 2015 on The Election Of Governors, Leaders And Mayors In Indonesia - Hamdy, Mohammad Zainal; Hamad, Mohammed Abdul Razaq (Syura: Journal of Law, 2024)
As the Islamic religion has been perfected by Allah SWT, Islam does not only regulate matters of worship and morals and the afterlife but also regulates worldly affairs including how to live socially and as a state. The Republic of Indonesia adopts a presidential system, namely the President as head of state and also as head of government, contained in the 1945 Constitution article 4 paragraph (1). The purpose of this study is to find out and compare how the leader election system in Indonesia is in accordance with Islam which is represented here by the thoughts of Imam Mawardi. This study uses a qualitative approach with a library method. The results show that the election and appointment of the Head are regulated in laws and regulations, both regarding administrative requirements and technical requirements. In a situation of political dynamics, it affects the substance of every change in laws and regulations that occur, so that the assumption that states that law is a political product is undeniable. This situation occurs in the legislation that regulates the election of Regional Heads which also experiences changes according to the political interests of the ruler. While the election in Islam in al-Mawardi's perception is by two methods, namely, the election of the head of state by the Ahlu al-hal wa al-aqdi institution or the people's representative council. Then the direct appointment of the head of state first. Then the comparison between the system of electing the head of state between the law and the figure of al-Mawardi is if we look at the times of Indonesia during the old order and the new order, there is relevance to al-Mawardi's view, namely the election of the head of state through representatives and direct appointment by the head of state first.